2021
DOI: 10.1139/apnm-2021-0220
|View full text |Cite
|
Sign up to set email alerts
|

Protocol-dependence of middle cerebral artery dilation to modest hypercapnia

Abstract: There is a need for improved understanding of how different cerebrovascular reactivity (CVR) protocols affect vascular cross-sectional area (CSA) when measures of vascular CSA are not feasible. In human participants, we delivered ~±4mmHg end-tidal partial pressure of CO2 (PETCO2) relative to baseline through controlled delivery, and measured changes in middle cerebral artery (MCA) cross-sectional area (CSA; 7 Tesla MRI), blood velocity (transcranial Doppler and Phase contrast MRI), and calculated CVR based on:… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Previous work ( Willie et al, 2011 ) clearly demonstrates that there is likely to be some degree of vasodilation induced by the increases in P ET CO 2 stimulated in the present study. Indeed, Al-Khazra et al ( Al-Khazraji et al, 2021 ) demonstrated that step changes in CO 2 altered the MCA diameter despite no change in MCA diameter during the ramp CO 2 stimulation, indicating that the protocol of the present study may have potentially underestimated CVR but it is unclear whether orthostatic stress modifies this limitation. The human brain has evolved heightened sensitivity to PaCO 2 /H+ (more so than PaO 2 ) that extends throughout the cerebrovasculature, from the large extracranial and intracranial conduit and middle cerebral arteries through to the smallest pial arterioles and parenchymal vessels, prioritizing the buffering of brain tissue pH for stabilization of chemosensory and autonomic control at the level of the brainstem ( Bailey et al, 2017 ).…”
Section: Limitationsmentioning
confidence: 60%
See 1 more Smart Citation
“…Previous work ( Willie et al, 2011 ) clearly demonstrates that there is likely to be some degree of vasodilation induced by the increases in P ET CO 2 stimulated in the present study. Indeed, Al-Khazra et al ( Al-Khazraji et al, 2021 ) demonstrated that step changes in CO 2 altered the MCA diameter despite no change in MCA diameter during the ramp CO 2 stimulation, indicating that the protocol of the present study may have potentially underestimated CVR but it is unclear whether orthostatic stress modifies this limitation. The human brain has evolved heightened sensitivity to PaCO 2 /H+ (more so than PaO 2 ) that extends throughout the cerebrovasculature, from the large extracranial and intracranial conduit and middle cerebral arteries through to the smallest pial arterioles and parenchymal vessels, prioritizing the buffering of brain tissue pH for stabilization of chemosensory and autonomic control at the level of the brainstem ( Bailey et al, 2017 ).…”
Section: Limitationsmentioning
confidence: 60%
“…Previous work(Willie et al, 2011) clearly demonstrates that there is likely to be some degree of vasodilation induced by the increases in P ET CO 2 stimulated in the present study. Indeed, Al-Khazra et al(Al-Khazraji et al, 2021) demonstrated that step changes in CO 2 altered the MCA diameter despite no change in MCA diameter during the ramp CO 2 stimulation, indicating that the protocol of the present study may have potentially underestimated CVR but it is unclear whether orthostatic stress modifies this limitation.…”
mentioning
confidence: 61%
“…However, TCD does not measure MCA diameter, and cerebral blood velocity is only an appropriate surrogate of CBF if vessel diameter remains constant. Although changes in MCA diameter may occur during steady state increases in of as little as 4.5 mmHg ( 37 ), TCD is considered an appropriate and practical tool to estimate CBF during exercise ( 15 ) and has been utilized in other work investigating MCAv kinetics during exercise in adults ( 2 , 3 , 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, our reliance on a ramp increase in arterial CO 2 instead of a stepwise increase is expected to reduce the bias inherent to this limitation. 21 Furthermore, we were not able to assess hyperemia to the brain, which may have influenced our findings. Given previous observations of ventilatory alterations after concussion, 36 comparisons related to ventilatory CO 2 sensitivity, in addition to the cerebrovascular responses to CO 2 changes as we investigated, may have been useful information.…”
Section: Limitationsmentioning
confidence: 94%
“…19,20 We use incremental hypercapnia rather than a step change in CO 2 induced by CO 2 rebreathing because the former captures cerebrovascular responses more reliably than the latter. 21 A finger photoplethysmography system (Finometer; Finapres Medical System) was used to measure beat-by-beat arterial pressure. CBF velocity was measured via transcranial Doppler (TCD) ultrasonography (2 MHz probe; MultiDop T2, DWL) at the M1 segment of the left or right middle cerebral arteries (MCAs) at a depth of 45-65 mm.…”
Section: Cerebral Vasoactivitymentioning
confidence: 99%